2020
DOI: 10.1186/s12944-020-01221-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein profiling in early multiple sclerosis patients: effect of chronic inflammation?

Abstract: Background: Inflammatory cytokines contribute to proatherogenic changes in lipid metabolism by reduction of HDLcholesterol (HDL-C) levels, impairment of its antiinflammatory and antioxidant functions. Therefore, the protective actions of HDL-C can be limited in chronic inflammatory diseases such as multiple sclerosis (MS). The aim of this study was to assess the association between lipoprotein subfractions and inflammatory status in early stages of multiple sclerosis.Methods: Polyacrylamide gel electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Reports related to FNG, NTZ, and IFN β-1a had mostly ADRs involving metabolic disorders, especially dyslipidemia, even if a retrospective observational study suggests that routine lipid profile monitoring is unnecessary during FNG treatment in MS patients without pre-existing cardiovascular comorbidities ( Rauma et al, 2020 ). A recent study has shown the correlation between MS-related systemic inflammation and the onset of mild dyslipidemia, especially in males in the early stages of the disease ( Rádiková et al, 2020 ). Moreover, dyslipidemia can influence, as a cardiovascular risk factor, the course of the disease, leading to a greater risk of progression to disability ( Kowalec et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reports related to FNG, NTZ, and IFN β-1a had mostly ADRs involving metabolic disorders, especially dyslipidemia, even if a retrospective observational study suggests that routine lipid profile monitoring is unnecessary during FNG treatment in MS patients without pre-existing cardiovascular comorbidities ( Rauma et al, 2020 ). A recent study has shown the correlation between MS-related systemic inflammation and the onset of mild dyslipidemia, especially in males in the early stages of the disease ( Rádiková et al, 2020 ). Moreover, dyslipidemia can influence, as a cardiovascular risk factor, the course of the disease, leading to a greater risk of progression to disability ( Kowalec et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…HDL lipoproteins are generally believed to be an atheroprotective component of plasma lipoproteins, but not all HDL subfractions exhibit this protective funtion. Some studies report potential atherogenic properties of small HDL subfractions [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study has several limitations. First, the major lipid fractions (HDL-C, LDL-C and TG) are each heterogeneous groups of particles defined by differences in particle size, density, apoprotein content, migration characteristics and relationships to disease, and these subfractions differ in their risk profiles 45 . This study was designed to investigate total blood lipid levels and thus did not consider whether there are subtypes of these fractions (e.g.…”
Section: Limitationsmentioning
confidence: 99%
“…This study was designed to investigate total blood lipid levels and thus did not consider whether there are subtypes of these fractions (e.g. LDL sub-particles) 45, 46 that might play different roles in MS risk or severity. Second The current study is unable to determine the underlying mechanism(s) for the potential causal relationship between RAC2 and MS risk; however, it is hoped that the findings presented may motivate further basic science investigations.…”
Section: Limitationsmentioning
confidence: 99%